Pengaruh Pendapatan Per Kapita Penggunaan Energi, Keterbukaan Perdagangan dan Kepadatan Penduduk terhadap Degradasi Lingkungan - Thahirah, At; Bashir, Abdul; Sari, Dwi Darma Puspita (Fakultas Ekonomi Universitas Samudra, 2025)
The study was conducted with the aim of analyzing the effect of per capita income, energy use, trade openness and population density on environmental degradation in BRICS and MINT countries and proving the validity of the Environmental Kuznets Curve (EKC) hypothesis. The data used is time series data during 2010-2022 and the cross-section consists of nine countries, namely Brazil, Russia, India, China, South Africa, Mexico, Indonesia, Nigeria, and Turkey. Data sources were obtained from the Global Carbon Atlas, World Bank, and Our World In Data using panel data regression analysis techniques. The results showed that per capita income, energy use, trade openness and population density had a positive and significant effect on environmental degradation, and proved the EKC hypothesis in BRICS and MINT countries even though it has not reached a turning point.